Association of Complete Blood Cell Count-Derived Inflammatory Biomarkers with Psoriasis and Mortality - Zhao Y; Yang XT; Bai YP; Li LF (Dove Medical Press, 2023)
Yang Zhao,1,2 Xu Tong Yang,1 Yan Ping Bai,3 Lin Feng Li2 1Department of Dermatology, Daxing Teaching Hospital, Capital Medical University, Beijing, 102600, People's Republic of China; 2Department of Dermatology, Beijing Friendship Hospital, Capital Medical University, Beijing, 100050, People's Republic of China; 3Department of Dermatology, China-Japan Friendship Hospital, Beijing, 100029, People's Republic of ChinaCorrespondence: Lin Feng Li, Department of Dermatology, Beijing Friendship Hospital, Capital Medical University, 95 Yong an Road, Xicheng District, Beijing, 100050, People's Republic of China, Email zoonli@sina.comBackground and Aim: Psoriasis is a persistent inflammatory disorder that affects 3% of the population and is associated with cardiovascular diseases. Therefore, this study aimed to investigate the correlations between complete blood cell count (CBC)-derived inflammatory biomarkers, psoriasis prevalence, and all-cause mortality.Methods: Data were obtained from the National Health and Nutrition Examination Survey (NHANES) spanning 2003- 2006 and 2009- 2014. Mortality data up to December 31, 2019 were obtained using the National Death Index. The following CBC-derived inflammatory biomarkers were examined: neutrophil/lymphocyte ratio (NLR), neutrophil/(white blood cells ˗ neutrophils) ratio (dNLR), monocyte count/lymphocyte ratio (MLR), (neutrophil + monocyte)/lymphocyte ratio (NMLR), platelet/lymphocyte ratio (PLR), and systemic inflammatory response index (SIRI). Weighted logistic and Cox regression analyses were used to calculate odds ratios, hazard ratios, and the corresponding 95% confidence intervals. Additionally, the prognostic value of the inflammatory indicators was assessed and ranked using the random survival forest approach.Results: In total, data from 21,431 participants with average age of 45.02 ± 0.27 years (49.51% male) were included in the study, among which 600 participants were positive for psoriasis (prevalence rate, 2.80%). Additionally, 79 all-cause deaths were recorded during a median follow-up period of 8.83 (6.67- 11.00) years. Moreover, NLR, dNLR, NMLR, PLR, and SIRI were positively associated with the prevalence of psoriasis. Furthermore, MLR, NMLR, and SIRI were positively correlated with all-cause mortality in patients with psoriasis, with NMLR being the most valuable predictor of all-cause mortality.Conclusion: CBC-derived inflammatory biomarkers were associated with psoriasis prevalence, NMLR, SIRI, and MLR values were associated with all-cause mortality in patients with psoriasis. Overall, assessment of these CBC-derived indicators may serve as a simple method for screening high-risk individuals among patients with psoriasis.Keywords: association, biomarker, inflammatory, NHANES, psoriasis